PERJUANGAN UMAT ISLAM MELALUI POLITIK DI INDONESIA - Mat Diah, Abdul Halim; Cholil, Muqoddam (Journal of Al-Tamaddun, 2008)
Islamic political struggle in Indonesia began in the year 1945 with the establishment Parti Islam Masyumi on November 7, 1945. Parti Islam Masyumi consists of Islamic organizations in Indonesia especially Nahdlatul Ulama and Muhammadiyah. It succeeded to gain the second place in the first Indonesian election in 1955 but finally dissolved by President Soekarno in 1960. With the coming of the New Order, Parti Islam Masyumi regained its role especially through Partai Persatuan Pembangunan. The replacement of the New Order with the reformation era led to the establishment of numerous Islamic Parties and they played important roles in political upheaval of Indonesia till present.